Kompleksnyj muľtiprofessionaľnyj podchod k lečeniju boľnych s akcentom na ispoľzovanije meneje častych metodov - Solár, Gustáv, 1947- (Pervaja klinika akupunktury i naturaľnoj mediciny G. Solara, 2022)
This international project - "Comprehensive multi-professional approach to the treatment of patients focusing on the use of less frequent methods" - is primary educational. As part of the European Union program Erasmus+, it has ambitions to fill current gaps in educating health professionals in possibilities for quality and comprehensive healthcare using less frequent methods in medicine. Such care is possible in both standard and emergency conditions, and the authors believe that, as such, it will also bring major benefits to everyone in contemporary medicine. This particular project is primarily educational in nature. It is designed for doctors, health professionals, physiotherapists, acoustic experts, symbologists, neuroscientists, biologists, physicists and other professionals who are somehow affected by this issue and are interested in future cooperation.